The Instructional Design For English At Integrated Islamic Elementary School Of Smart Cendekia Karanganom, Klaten: A Naturalistic Study - Sutrisno, Sutrisno; , Prof. Endang Fauziati, M.Hum; , Dr. Phil. Dewi Candraningrum, M.Ed (2014)
English has become the main device as a bridge of international communication. The existence of English at Integrated Islamic Elementary School (SDIT) of Smart Cendekia Karanganom includes a recent issue which has invited much attention to Education and Culture Ministry. Departing with the phenomenon, the existence of instructional design is obviously needed in English teaching specially in Elementary School. The research problem of the study was how the instructional design of English teaching at SDIT Smart Cendekia Karanganom. The objectives of the study are to describe the instructional design of English teaching at SDIT Smart Cendekia that encompasses instructional material, syllabus, learning objective, method of teaching, and Teaching evaluation. The research is naturalistic study. The efforts of study overview notional-functional syllabus which are categorized into novice, elementary, intermediate level. The learning objectives are general and specific learning outcome. The instructional material is divided into printed and visual material. Teaching design is divided into Teacher's role, student's role, classroom procedure and classroom activities. Media are grouped into two forms: The first is printed media such as picture, white envelop and colorful paper. The second is unprinted media that entails slide. The evaluation describes evaluation model and kind of evaluation. The evaluation models are dialogue completion task, multiple choice and reading task. The kind of evaluation involves formative and summative evaluation. Relied on the finding, discussion, conclusion and implication, the writer suggests for English teacher to encourage students' engagement in the classroom. The application of diverse methods, technique are obviously needed in English teaching. The writer also recommends for future researcher to expand the study in other research field.